A method for preparing a low-hardness ceramic-based high-temperature sealing coating

By using anhydrous ethanol, YSZ powder and silica-containing garnet powder, combined with ball milling, drying, sintering and plasma spraying technology, a low-hardness ceramic-based high-temperature sealing coating was prepared, which solved the ceramic-based high-temperature sealing coating The problem of increased coating hardness improves wearability and thermal cycle life, and achieves the improvement of safety and efficiency.

CN116986898BActive Publication Date: 2024-12-27CIVIL AVIATION UNIV OF CHINA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310969661.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2024-12-27
Estimated Expiration
2043-08-03

AI Technical Summary

Technical Problem

The existing ceramic-based high-temperature sealing coating has a rapid increase in hardness under high temperature environments, resulting in the threat of the safety of rotor blades and aircraft engines. Common methods such as adding pore-forming phases or adjusting spraying processes have low deposition efficiency, impurities introduction and sintering densification. The problem.

Method used

The ceramic-based raw materials composed of anhydrous ethanol, YSZ powder and silica-containing garnet powder were prepared by ball milling, drying, sintering and mechanical crushing and screening, and combined with plasma spraying, low-hardness ceramic-based high-temperature sealing in loose areas were prepared. The coating avoids the introduction and sintering of impurities in the addition of pore-forming materials and high-temperature treatment.

Benefits of technology

A low-cost and simple preparation process is achieved, which significantly reduces the hardness of the ceramic-based high-temperature sealing coating, improves the wearability performance and thermal cycle life, and avoids the safety hazards of increased hardness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116986898B_ABST
    Figure CN116986898B_ABST
Patent Text Reader

Abstract

A method for preparing a low-hardness ceramic-based high-temperature sealing coating. The method comprises the following steps: obtaining YSZ ceramic-based composite material powder containing silicon garnet; separating the ball material by a vibrating screen machine; high-temperature sintering treatment; mechanical crushing and screening treatment; and preparing a low-hardness ceramic-based high-temperature sealing coating by a plasma spraying method. The advantages of the present invention are: low cost and a relatively simple preparation process. The addition of low-melting-point silicon-containing garnet forms a uniformly and diffusely distributed loose area in the microstructure of the plasma-sprayed ceramic-based coating, and the loose area is composed of molten silicon-containing garnet and unmelted ceramic material. On the one hand, the loose area has a pore-like function, which can significantly reduce the hardness of the ceramic-based high-temperature sealing coating prepared by the silicon-containing garnet composite ceramic powder, thereby improving the wear resistance; on the other hand, the loose area has a certain crack initiation and expansion inhibition function, thereby improving the thermal cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic functional coating structure design and optimization, and in particular relates to a method for preparing a low-hardness ceramic-based high-temperature sealing coating. Background Art

[0002] Sealing coating is a kind of functional coating applied to the gap control part of the airflow channel of the aircraft engine. On the one hand, it can reduce the operating gap, effectively reduce the radial airflow loss, and improve the working efficiency of the aircraft engine. On the other hand, the good abradability of the sealing coating can protect the rotor blades from collision and wear damage during operation. In order to be suitable for the ambient temperature of the airway sealing channel of different parts of the aircraft engine compressor, turbine, etc., a series of sealing coatings with stable performance such as low temperature (<400℃, such as aluminum silicon polyphenyl ester coating), medium temperature (400℃~800℃, such as nickel graphite coating, nickel chromium aluminum diatomite coating, etc.) and high temperature alloy with heat resistance temperature below 1000℃ have been developed at home and abroad. With the increase of thrust-to-weight ratio of advanced aircraft engines, the temperature before the turbine continues to rise, resulting in the airflow temperature of the airway sealing part of the high-temperature end of the aircraft engine exceeding 1000℃. Therefore, the commonly used alloy series sealing coatings can no longer meet the service requirements. High temperature resistant (working stably for a long time at more than 1000℃) and abradable ceramic-based sealing coatings have become the most advanced airway sealing structure at present, and are also one of the research hotspots and urgent needs of high-performance aircraft engines.

[0003] As a kind of "self-sacrificing" functional coating, ceramic-based sealing coating needs to maintain a low hardness and good abradability throughout the service life to prevent damage to the rotor blades during collision or scraping with the rotor blades, so as to ensure the safety of the aircraft engine. In order to obtain a lower hardness, researchers usually use the method of adding pore-forming phase or adjusting the spraying process. Among them, the basic principle of the method of adding pore-forming phase is to first add pore-forming materials (polyphenylene ester, polyimide, etc.) that are easy to decompose and burn at high temperature into the ceramic-based high-temperature sealing coating, and then use the high-temperature treatment method to burn the pore-forming materials such as polyphenylene ester or polyimide in the coating, thereby forming a porous ceramic-based sealing coating. The basic principle of adjusting the spraying process method is to increase the degree of mutual interlacing of deformed particles by adjusting key factors such as the particle size distribution, powder feeding rate, spraying power and spraying distance of the ceramic-based powder, thereby forming a stacking gap, thereby improving the porosity of the ceramic-based sealing coating.

[0004] However, the commonly used method of adding pore-forming phase to reduce the hardness of ceramic-based sealing coating has the following three limitations: First, the addition of pore-forming material will significantly reduce the deposition efficiency of ceramic-based sealing coating. This is because the thermal stability temperature of commonly used organic pore-forming materials is generally lower than 400°C, which is much lower than the temperature of plasma jet (more than 10,000°C). Therefore, organic pore-forming materials will inevitably burn out in large quantities in plasma jet, which reduces the deposition efficiency of coating, increases the manufacturing cost of coating, and causes serious waste of resources. Second, the preparation process of adding pore-forming phase is complicated and easy to introduce impurities. This is because the main steps of this method are: in the first step, agglomerated powder containing pore-forming material needs to be prepared by spray granulation. The spray granulation process has complicated steps, long time, low efficiency, and inevitably introduces other impurities. The reasons are: ① The pore-forming material, solvent and ceramic material need to be ball-milled and mixed for a long time; ② Drying treatment is performed and the powder and grinding balls after ball milling are separated; ③ Necessary functional components such as adhesives and dispersants are added and configured into a slurry suspension with the ball-milled materials. This process requires a long time. Mechanical stirring and heating; ④ Use the spray granulation method to prepare the agglomerated powder containing the pore-forming material. For the sealing coating powder containing the pore-forming material, the high-temperature sintering method cannot be used to remove the dispersant and the adhesive, because the high-temperature sintering will also burn the pore-forming material while removing the dispersant and the adhesive. Therefore, the agglomerated powder inevitably contains other functional components in the slurry; the second step is to use the plasma spraying method to prepare the ceramic-based coating containing the pore-forming material; the third step is to use the high-temperature treatment method to remove the pore-forming material in the ceramic-based coating, and finally obtain a porous and low-hardness ceramic-based high-temperature sealing coating. Third, the ceramic-based porous structure obtained by this method will inevitably have sintering densification problems under the action of high temperature for a long time, and with the extension of time, the degree of densification becomes more serious, which will cause the coating hardness to rise rapidly, thereby seriously threatening the safety of the rotor blades and the safety of the entire aircraft engine.

[0005] The method of reducing the hardness of the ceramic-based sealing coating by adjusting the spraying process also has the following two limitations: First, the effect of increasing the porosity of the coating by adjusting the preparation process of the ceramic-based sealing coating is limited. This is because the particle size distribution and preparation process of the raw materials of the ceramic-based sealing coating are also key factors affecting the performance of the thermal spray coating. Although the method of adjusting the preparation process of the ceramic-based sealing coating can increase the porosity of the coating and reduce the hardness of the coating to a certain extent, the selection of powder with larger particle size or lower spraying power often sacrifices other aspects of the performance of the ceramic-based sealing coating and reduces the durability of the ceramic-based sealing coating. Second, the ceramic-based porous structure obtained by this method will inevitably have the problem of sintering densification under the action of high temperature for a long time, and the degree of densification will become more serious with the extension of time, which will cause the hardness of the coating to rise rapidly, seriously threatening the safety of the rotor blades and the safety of the entire aircraft engine. Summary of the invention

[0006] In order to solve the above problems, the object of the present invention is to provide a method for preparing a low-hardness ceramic-based high-temperature sealing coating.

[0007] In order to achieve the above object, the method for preparing a low-hardness ceramic-based high-temperature sealing coating provided by the present invention comprises the following steps performed in sequence:

[0008] 1) crushing and uniformly mixing anhydrous ethanol, YSZ (yttria-stabilized zirconia) powder, and silicon-containing garnet powder into a YSZ ceramic-based raw material using a ball mill to obtain a YSZ ceramic-based composite material powder containing silicon garnet; wherein the amount ratio of anhydrous ethanol, YSZ powder, and silicon-containing garnet powder is 150-200 ml: 150-200 g: 20-30 g;

[0009] 2) drying the YSZ ceramic-based composite material powder containing silicon garnet, and separating the ball material by using a vibrating screen machine;

[0010] 3) subjecting the YSZ ceramic-based composite material powder containing silicon garnet after the ball material is separated to high-temperature sintering treatment;

[0011] 4) Mechanically crushing and screening the YSZ ceramic-based composite material powder containing silicon garnet after high-temperature sintering;

[0012] 5) The YSZ ceramic-based composite material powder containing silicon garnet after screening is sprayed on the gap control part of the airflow channel of the aircraft engine by plasma spraying method, so as to prepare a low-hardness ceramic-based high-temperature sealing coating containing loose areas, low hardness and microcrack growth inhibition function.

[0013] In step 1), the rotation speed of the ball mill is 500-600 r / min, 200-300 g of ZrO2 grinding balls are used, and the ball milling time is 6-8 h.

[0014] In step 2), the drying temperature is 100-120° C., the drying time is 120-180 min, the standard mesh number of the vibrating screen is 60-100 mesh, and the sieving time is 10-20 min.

[0015] In step 3), the sintering temperature is 1200-1300° C., and the sintering time is 300-360 min.

[0016] In step 4), the mechanical crushing is performed by using a FW100 crusher, the crushing time is 300 to 360 seconds, and the screening is performed by using a standard sieve of 100 mesh and 200 mesh, and the screening time is 5 to 7 minutes.

[0017] In step 5), the voltage of the plasma spraying is 38-39V, the current is 790-800A, the spraying distance is 120-130mm, and the powder feeding rate is 5-6r / min.

[0018] The method for preparing a low-hardness ceramic-based high-temperature sealing coating provided by the present invention has the following advantages:

[0019] (1) Low cost and simple preparation process. In the powder preparation process, it is not necessary to add various functional components such as pore-forming materials, dispersants, adhesives, etc., and it is not necessary to prepare slurry and stir at high temperature and high speed for a long time. It only needs to be treated at high temperature for a certain period of time in an air atmosphere to obtain a composite ceramic powder containing silicon garnet. After plasma spraying, it is not necessary to perform high temperature treatment to remove the pore-forming materials, and a ceramic-based high-temperature sealing coating with low hardness can be obtained.

[0020] (2) The addition of low-melting-point silicon-containing garnet forms a uniform and diffusely distributed loose area in the microstructure of the plasma sprayed ceramic-based coating. The loose area is composed of molten silicon-containing garnet and unmelted ceramic material. On the one hand, the loose area has a pore-like function, which can significantly reduce the hardness of the ceramic-based high-temperature sealing coating prepared by silicon-containing garnet composite ceramic powder and improve the wear resistance; on the other hand, the loose area has a certain crack initiation and expansion inhibition function, which improves the thermal cycling performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The present invention provides a microscopic morphology of the YSZ ceramic-based composite material powder containing silicon garnet, wherein the magnifications of (a) and (b) are 50 and 1000 respectively, and (c) is the energy spectrum detection result of the spherical particles in the microscopic morphology.

[0022] Figure 2The metallographic examination results and scanning electron microscope examination results of the microstructure of the low-hardness ceramic-based high-temperature sealing coating provided by the present invention, wherein (a) is the metallographic microstructure, (b) is the scanning electron microscope microstructure, (c) is the energy spectrum examination result of the loose area in the scanning electron microscope microstructure, and (d) is the energy spectrum examination result of the dense area in the scanning electron microscope microstructure.

[0023] Figure 3 The results of indentation crack growth in the microstructure of the low-hardness ceramic-based high-temperature sealing coating provided by the present invention, wherein (a) is the indentation and crack growth behavior near the loose area, and (b) is the indentation and crack growth behavior away from the loose area. DETAILED DESCRIPTION

[0024] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0025] Embodiment 1:

[0026] The method for preparing a low-hardness ceramic-based high-temperature sealing coating provided in this embodiment comprises the following steps performed in sequence:

[0027] 1) Preparation of YSZ ceramic-based composite material powder containing silicon garnet: YSZ ceramic-based raw materials consisting of anhydrous ethanol, YSZ powder ST-O-006-2, and silicon-containing garnet powder ST-YAG-001 were crushed and mixed uniformly using a ball mill to prepare YSZ ceramic-based composite material powder containing silicon garnet. The amount ratio of anhydrous ethanol, YSZ powder, and silicon-containing garnet powder was 150ml: 150g: 20g; the speed of the ball mill was 500r / min, the ZrO2 grinding ball was 200g, and the ball milling time was 6h.

[0028] 2) Separation of powder and ball material of YSZ ceramic matrix composite material containing silicon garnet: The powder of YSZ ceramic matrix composite material containing silicon garnet is dried at a temperature of 100° C. for 120 min; and the ball material is separated by a vibrating sieve machine with a standard sieve mesh of 60 mesh and a sieving time of 10 min.

[0029] 3) High temperature sintering treatment of YSZ ceramic matrix composite material powder containing silicon garnet: After separating the ball material, the YSZ ceramic matrix composite material powder containing silicon garnet is subjected to high temperature sintering treatment, the sintering temperature is 1200° C., and the sintering time is 300 min.

[0030] 4) Mechanical crushing and screening of YSZ ceramic-based composite material powder containing silicon garnet: The YSZ ceramic-based composite material powder containing silicon garnet after high-temperature sintering was mechanically crushed using a FW100 crusher for 300 seconds; and was screened using standard sieves of 100 mesh and 200 mesh for 5 minutes.

[0031] 5) Preparation of low-hardness ceramic-based high-temperature sealing coating: The sieved silicon garnet-containing YSZ ceramic-based composite material powder is sprayed on the gap control part of the airflow channel of the aircraft engine by plasma spraying. The plasma spraying voltage is 38V, the current is 790A, the spraying distance is 120mm, and the powder feeding rate is 5r / min, thereby preparing the low-hardness ceramic-based high-temperature sealing coating.

[0032] Embodiment 2:

[0033] The method for preparing a low-hardness ceramic-based high-temperature sealing coating provided in this embodiment comprises the following steps performed in sequence:

[0034] 1) Preparation of YSZ ceramic-based composite material powder containing silicon garnet: YSZ ceramic-based raw materials composed of YSZ powder ST-O-006-2 and silicon-containing garnet powder ST-YAG-001 were crushed and mixed uniformly by a ball mill to prepare YSZ ceramic-based composite material powder containing silicon garnet. The amount ratio of anhydrous ethanol, YSZ powder, and silicon-containing garnet powder was 175:175g:25g; the speed of the ball mill was 550r / min, the ZrO2 grinding ball was 250g, and the ball milling time was 7h.

[0035] 2) Separation of powder and ball material of YSZ ceramic matrix composite material containing silicon garnet: The powder of YSZ ceramic matrix composite material containing silicon garnet is dried at a temperature of 110° C. for 150 min; and the ball material is separated by a vibrating sieve machine with a standard sieve mesh of 80 mesh and a sieving time of 15 min.

[0036] 3) High temperature sintering treatment of YSZ ceramic matrix composite material powder containing silicon garnet: After separating the ball material, the YSZ ceramic matrix composite material powder containing silicon garnet is subjected to high temperature sintering treatment, the sintering temperature is 1250° C., and the sintering time is 330 min.

[0037] 4) Mechanical crushing and screening of YSZ ceramic-based composite material powder containing silicon garnet: The YSZ ceramic-based composite material powder containing silicon garnet after high-temperature sintering was mechanically crushed using a FW100 crusher for 330 seconds; and was screened using standard sieves of 100 mesh and 200 mesh for 6 minutes.

[0038] 5) Preparation of low-hardness ceramic-based high-temperature sealing coating: The sieved silicon garnet-containing YSZ ceramic-based composite material powder is sprayed on the gap control part of the airflow channel of the aircraft engine by plasma spraying. The plasma spraying voltage is 38.5V, the current is 795A, the spraying distance is 125mm, and the powder feeding rate is 5.5r / min, thereby preparing the low-hardness ceramic-based high-temperature sealing coating.

[0039] Embodiment 3:

[0040] The method for preparing a low-hardness ceramic-based high-temperature sealing coating provided in this embodiment comprises the following steps performed in sequence:

[0041] 1) Preparation of YSZ ceramic-based composite material powder containing silicon garnet: YSZ ceramic-based raw materials consisting of anhydrous ethanol, YSZ powder ST-O-006-2, and silicon-containing garnet powder ST-YAG-001 were crushed and mixed uniformly using a ball mill to prepare YSZ ceramic-based composite material powder containing silicon garnet. The amount ratio of anhydrous ethanol, YSZ powder, and silicon-containing garnet powder was 200ml: 200g: 30g; the speed of the ball mill was 600r / min, the ZrO2 grinding ball was 300g, and the ball milling time was 8h.

[0042] 2) Separation of ball material from YSZ ceramic matrix composite powder containing silicon garnet: The YSZ ceramic matrix composite powder containing silicon garnet is dried at 120°C for 180 min; and the ball material is separated by a vibrating sieve machine with a standard sieve mesh of 100 mesh and a sieving time of 20 min.

[0043] 3) High temperature sintering treatment of YSZ ceramic matrix composite material powder containing silicon garnet: After separating the ball material, the YSZ ceramic matrix composite material powder containing silicon garnet is subjected to high temperature sintering treatment, the sintering temperature is 1300° C., and the sintering time is 360 min.

[0044] 4) Mechanical crushing and screening of YSZ ceramic-based composite material powder containing silicon garnet: The YSZ ceramic-based composite material powder containing silicon garnet after high-temperature sintering was mechanically crushed using a FW100 crusher for 360 seconds; and was screened using standard sieves of 100 mesh and 200 mesh for 7 minutes.

[0045] 5) Preparation of low-hardness ceramic-based high-temperature sealing coating: The sieved silicon garnet-containing YSZ ceramic-based composite material powder is sprayed on the gap control part of the airflow channel of the aircraft engine by plasma spraying. The plasma spraying voltage is 39V, the current is 800A, the spraying distance is 130mm, and the powder feeding rate is 6r / min, thereby preparing the low-hardness ceramic-based high-temperature sealing coating.

[0046] Figure 1 The microscopic morphology of the YSZ ceramic matrix composite material powder containing silicon garnet provided in the embodiment of the present invention, wherein the magnifications of (a) and (b) are 50 and 1000 respectively, and (c) is the energy spectrum detection result of the spherical particles in the microscopic morphology. Figure 1 As can be seen from (a), the YSZ ceramic-based composite material powder containing silicon garnet prepared by the present invention is in an irregular polyhedral shape, with a relatively uniform particle size and an average particle size of about 100 μm; Figure 1 (b) and Figure 1 (c) Analysis shows that the YSZ particles undergo spheroidization during the sintering process. The microstructure of the YSZ ceramic-based composite material powder containing silicon garnet is composed of a large number of spherical YSZ particles. The powder composed of this spherical microstructure has less resistance in the plasma jet, which is beneficial to the fluidity of the YSZ ceramic-based composite material powder containing silicon garnet, thereby improving the sprayability of the powder.

[0047] Figure 2 The metallographic test results and scanning electron microscope test results of the microstructure of the low-hardness ceramic-based high-temperature sealing coating provided in the embodiment of the present invention, wherein (a) is the metallographic microstructure, (b) is the scanning electron microscope microstructure, (c) is the energy spectrum test result of the loose area in the scanning electron microscope microstructure, and (d) is the energy spectrum test result of the dense area in the scanning electron microscope microstructure. Figure 2 (a) and Figure 2 As can be seen in (b), the microstructure of the low-hardness ceramic-based high-temperature sealing coating is mainly composed of dense areas and loose areas; Figure 2 (c) and Figure 2 (d) is the scanning electron microscope and energy spectrum detection results. Figure 2 From the analysis in (c), it can be seen that the dense area in the microstructure of the low-hardness ceramic-based high-temperature sealing coating is mainly YSZ ceramics; Figure 2 From the analysis in (d), it can be seen that the loose area in the microstructure of the low-hardness ceramic-based high-temperature sealing coating is mainly a mixture of YSZ ceramics and silicon-containing garnet. This is because the melting point of YSZ is as high as about 2700℃, while the melting point of silicon-containing garnet is only about 1950℃. In the plasma jet, the silicon-containing garnet material with a lower melting point is easily heated to a molten state. This molten silicon-containing garnet has the function of adhering to or wrapping the unmelted YSZ particles with a higher melting point. When the silicon-containing garnet particles adhering to or wrapping the unmelted YSZ particles collide and spread to form a coating, it is easy to form a loose area containing a mixture of YSZ ceramics and silicon-containing garnet.

[0048] Figure 3The results of indentation crack growth in the microstructure of the low-hardness ceramic-based high-temperature sealing coating provided by the embodiment of the present invention, where (a) is the indentation and crack growth behavior near the loose area, and (b) is the indentation and crack growth behavior away from the loose area. Figure 3 From the analysis in (a), it can be seen that when the indentation is close to the loose area, fewer cracks are initiated around the indentation near the loose area; Figure 3 From the analysis in (b), it can be seen that when the indentation is far away from the loose area, a large number of microcracks are generated at the indentation tip, and when the cracks extend to the loose area, the cracks undergo obvious deflection or termination.

[0049] The hardness of the low-hardness ceramic-based high-temperature sealing coating provided by the present invention is comparable to that of the conventional coating prepared by adding pore-forming materials, and has good wearability, which indicates that the loose area (formed based on the adhesion and wrapping effect of the molten silicon-containing garnet on the unmelted YSZ particles) in the low-hardness ceramic-based high-temperature sealing coating provided by the present invention has a "hole-like" function. At the same time, the thermal cycle life of the low-hardness ceramic-based high-temperature sealing coating provided by the present invention is improved by more than 50% compared with the conventional coating prepared by adding pore-forming materials, because the "loose area" in the low-hardness ceramic-based high-temperature sealing coating can consume thermal cycle energy during the thermal cycle process, release the driving force for crack initiation and expansion, thereby improving the thermal cycle life of the low-hardness ceramic-based high-temperature sealing coating.

Claims

1. A method for preparing a low-hardness ceramic-based high-temperature sealing coating, characterized in that: The method for preparing the low-hardness ceramic-based high-temperature sealing coating comprises the following steps performed in sequence: 1) Using a ball mill to crush and evenly mix a YSZ ceramic-based raw material consisting of anhydrous ethanol, YSZ powder, and silicon garnet powder, to obtain a YSZ ceramic-based composite material powder containing silicon garnet; wherein the amount ratio of anhydrous ethanol, YSZ powder, and silicon garnet powder is 150-200 ml: 150-200 g: 20-30 g; 2) drying the YSZ ceramic matrix composite material powder containing silicon garnet, and separating the ball material by using a vibrating screen; 3) subjecting the YSZ ceramic matrix composite material powder containing silicon garnet after the ball material is separated to high temperature sintering treatment; 4) Mechanically crushing and sieving the YSZ ceramic matrix composite material powder containing silicon garnet after high temperature sintering to 100 mesh and 200 mesh; 5) The YSZ ceramic-based composite material powder containing silicon garnet after screening is sprayed on the gap control part of the airflow channel of the aircraft engine by plasma spraying method, so as to prepare a low-hardness ceramic-based high-temperature sealing coating containing loose areas, low hardness and micro-crack growth inhibition function; In step 3), the sintering temperature is 1200-1300°C, and the sintering time is 300-360 minutes; In step 5), the voltage of the plasma spraying is 38-39V, the current is 790-800A, the spraying distance is 120-130mm, and the powder feeding rate is 5-6r / min.

2. The method for preparing a low-hardness ceramic-based high-temperature sealing coating according to claim 1, characterized in that: In step 1), the rotation speed of the ball mill is 500-600 r / min, 200-300 g of ZrO2 grinding balls are used, and the ball milling time is 6-8 h.

3. The method for preparing a low-hardness ceramic-based high-temperature sealing coating according to claim 1, characterized in that: In step 2), the drying temperature is 100-120° C., the drying time is 120-180 min, the standard mesh number of the vibrating screen is 60-100 mesh, and the sieving time is 10-20 min.

4. The method for preparing a low-hardness ceramic-based high-temperature sealing coating according to claim 1, characterized in that: In step 4), the mechanical crushing adopts FW100 type crusher, the crushing time is 300-360s, and the screening is carried out using 100 mesh and 200 mesh standard sieves, and the screening time is 5-7min.

Citation Information

Patent Citations

  • Plasma spraying YSZ ceramic-based sealing coating preparation method capable of improving deposition rate

    CN114351080A